Persepsi Guru terhadap Implementasi Asesmen Diagnostik dalam Pembelajaran yang Berpusat pada Siswa Sekolah Dasar - Nissa, Khoirrun; Nurbadriyah, Faradilah; Jayanti, Sasti Nanda; Firdausa, Rossa Ayudyah; Sa'diyah, Halimatus; Darmawan, Puguh; Kusumawardani, Albertina (Journal of Innovation and Teacher Professionalism, 2024)
Penelitian ini bertujuan mendeskripsikan persepsi guru terhadap Asesmen Diagnostik dalam Pembelajaran di SDN Sawojajar 6 Kota Malang. Metode kualitatif digunakan. Data diperoleh melalui wawancara semi berstruktur dengan lembar kisi-kisi instrumen. Analisis deskriptif kualitatif dilakukan terhadap data. Hasil menunjukkan pentingnya perencanaan dan pelaksanaan asesmen diagnostik. Pengetahuan guru tentang peserta didik menjadi dasar rancangan asesmen. Asesmen dilakukan pada awal pembelajaran menggunakan angket dan observasi untuk memetakan kemampuan dan kebutuhan peserta didik. Analisis hasil membantu menyusun pembelajaran sesuai dan memberikan umpan balik. Keberhasilan dipengaruhi oleh kesadaran guru, relevansi konten, kesesuaian dengan perkembangan, dan kejujuran peserta didik. Dengan memperhatikan faktor-faktor tersebut, asesmen diagnostik mendukung pembelajaran inklusif di sekolah dasar. Kata kunci: asesmen diagnostik, tingkat pemahaman, peserta didik Teachers' Perceptions of the Implementation of Diagnostic Assessments in Elementary School Student’s Centered Learning This research aims to describe teachers' perceptions of Diagnostic Assessment in Learning at SDN Sawojajar 6, Malang City. Qualitative methods were employed. Data were obtained through semi-structured interviews with instrument grids. Qualitative descriptive analysis was conducted on the data. The results indicate the importance of planning and implementing diagnostic assessments. Teachers' knowledge of students forms the basis of assessment design. Assessments are conducted at the beginning of learning using questionnaires and observations to map students' abilities and needs. Analysis of the results helps in designing appropriate learning and providing feedback. Success is influenced by teachers' awareness, content relevance, alignment with development, and students' honesty. Considering these factors, diagnostic assessments support inclusive learning in elementary schools. Keyword: diagnostic assessment, level of understanding, students